Implementasi Metode Human-Centered Design (HCD) dalam Transformasi Digital Layanan Adminduk: Redesign Layanan Berbasis WhatsApp ke Portal Terintegrasi (Studi Kasus: Disdukcapil Polewali Mandar) - Diny Anggriani Adnas; Uswatun Hasanah; Nur Jayanti Putri S3 (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2026)
The digital transformation of population administration (Adminduk) services in Polewali Mandar currently relies heavily on WhatsApp-based service innovations. While accessible, this model creates significant usability issues: unstructured service flows, lacks transparency in status tracking, and places a burden on both users and operators. This research aims to redesign this chat-based service into an efficient, integrated service portal. The method used is Human-Centered Design (HCD). This process involves qualitative analysis to map the User Journey Map and identify critical pain points within the current WhatsApp service flow. These findings will form the basis for designing a high-fidelity prototype of a service portal. The expected outcome is a functional Adminduk portal prototype that demonstrates an intuitive guided flow and transparent status tracking features. This design offers a concrete solution for the digital transformation of Adminduk services to be more accountable and user-centered.